Characterization of UV-light-driven AG/BIOCL nanoplates synthesized by sonochemical deposition method - A. Phuruangrat (2020)
© 2020, S.C. Virtual Company of Phisics S.R.L. All rights reserved. In this study, a facile strategy for the fabrication of Ag/BiOCl nanoplates for photodegradation of methylene blue (MB) under UV light irradiation is reported. BiOCl nanoplates were synthesized by simple hydrothermal method. Ag nanoparticles were deposited on BiOCl nanoplates in ethylene glycol as a solvent by sonochemical method. The as-prepared samples were characterized by X-ray diffraction (XRD), scanning electron microscopy (SEM), transmission electron microscopy (TEM), selected area electron diffraction (SAED) and X-ray photoelectron spectroscopy (XPS). The results showed that cubic Ag nanoparticles were uniformly deposited on tetragonal BiOCl nanoplates. The Ag/BiOCl heterostructures showed significantly enhanced photocatalytic performance in the degradation of methylene blue (MB) comparing with the BiOCl nanoplates. The observed degradation of MB over 10 wt% Ag/BiOCl photocatalyst was 0.011 min–1 which is 4.58 times of that over pure BiOCl nanoplates.